136Xe enrichment through cryogenic distillation. (28th September 2017) - Back, H.O.; Bottenus, D.R.; Clayton, C.; Stephenson, D.; TeGrotenhuis, W.
Abstract: The next generation of 136 Xe neutrinoless double beta decay experiments will require on the order of 5 tons of enriched 136 Xe. By estimating the relative volatilities of the xenon isotopes and using standard chemical engineering techniques we explore the feasibility of using cryogenic distillation to produce 5 tons of 80% enriched 136 Xe in 5–6 years. With current state-of-the-art distillation column packing materials we can estimate the total height of a traditional cryogenic distillation column. We also report on how Micro Channel Distillation may reduce the overall size of a distillation system for 136 Xe production.